Environmental control and waste disposal - B A Koch; G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1974)
A system for aerobic oxidation of waste has been used continuously since 1968 and is now functioning successfully. Figure 11.1 shows general design of the units. Originally "paddle wheels" were used to circulate liquid waste, keep solids in suspension, and mix oxygen into the liquid. Their performance, however, was less than desirable. Excessive foaming of liquid in the pits kept recurring, and maintenance of "paddle wheels" was expensive and time consuming.; Swine Day, Manhattan, KS, November 14, 1974
Keywords: Swine day; 1974; Kansas Agricultural Experiment Station contribution; no. 483; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 221; Swine; Environmental control; Waste disposal